STUDY OF THE ACTIVITY EXTRACTS FROM SAUSSUREA CONTROVERSA AND FILIPENDULA ULMARIA IN EXPERIMENTAL OSTEOMYELITIS WITH THREE-PHASE SCINTIGRAPHY - Ye. Yu. Avdeeva; M. A. Zorkaltsev; V. D. Zavadovskaya; G. V. Slizovsky; Ye. A. Krasnov; V. G. Pekhenko; M. Yu. Stepanov (Бюллетень сибирской медицины, 2015)
The activity of extracts from Saussurea controversa DC and Filipendula ulmaria (L.) Maxim studied on experimental osteomyelitis by means of 3-phase scintigraphy. The use of aqueous-ethanolic extracts of the aerial parts of plants helps to reduce the fixation of the radiopharmaceutical in the affected area and what characterizes their positive impact on the disease. These plants are promising objects for study of medicines the treatment of osteomyelitis.